Mitochondrial dysfunction affects chloroplast functions - Busi, María Victoria (2011)
The transcriptomic response of A9:u-ATP9 and apetala3:u-ATP9 lines carrying a mitochondrial dysfunction in flower tissues has been characterized. Both lines showed an alteration in the transcription of several genes involved in carbon and nitrogen metabolism, stress responses, transcription factors and DNA binding proteins. Interestingly, several transcripts of photosynthetic-related genes were also affected in their expression such as the mRNA s encoding for chlorophyllase, chlorophyll binding proteins and a PSII . Moreover, chlorophyll levels were reduced and the Mg-dechelatase activity was increased, indicating an alteration in chlorophyll metabolism. Our results suggest that the mitochondrial dysfunction may also affect chloroplastic functions, and that our model could be useful to uncover retrograde signaling mechanisms operating between the three different plant genomes.